People VS Bureaucracies in the 2020's - Avny, Amos (IJRDO-Journal of Applied Science, 2015)
The world of 2020's differs significantly from the previous century. It isnatural, therefore, that people will call for changing also the Public Administrationand all the governance establishment. The paper below discusses someparadigmatic changes required for improving the existing system. Further, itexplores the direct and non-direct democratic way of representation, which can beimproved by using the new advanced communication technology. Later the Authorshortly discusses the E-Government future potential. He also emphasizes hisrecommendation for making public service a much more people oriented and humancentric system. Finally, the Author suggests to introduce into the existingbureaucracies a mandatory by-pass mechanism that will enable circumventingmost of the system's unnecessary built-in obstacles.The mandatory by-pass mechanism will be built of two levels exceptionalcommittees, one at the field level and one of the appeal one and will be staffed bycurrent and retired employees.